Pluralistic Islamic cities and the significance of Marrakesh declaration - Mya, Su San; Ismail, Noor Atiah (Science Publishing Corporation, 2019)
If Quran offers the timeless guidance and Sunnah (the way of Prophet Muhammad) is the truthful way, the study on how to improve the planning methods according to Islamic Principles would be of immense help to a nation. Without a doubt Exemplary Islamic City is the goal we are aiming for. But how are we going to deal with pluralism in our planning methods while balancing between modern and Islamic notions? Traditionally in Islam, Muslims are obliged to respect and protect the people regardless of their faith and background. For the very reason that it promotes peace and tolerance, many other groups joined for Islamic path even in the hardest of times according to the history. A peaceful nation state is where everyone can be included in managing the affairs of their own society, in accordance with their rights and duties, to be outlined by a reasonable constitution that seeks harmonious living, the rule of law. Does Islam recognized those values? Yes it does, and even more so, the very first functioning constitution was developed in early days of Islam which later known as The Medina Charter (Shahifat al-Medina). The Medina Charter, prepared as the basis of the Medina city-state established by Prophet Muhammad, was the first written constitution in Islam and arguably the first instance of constitutional law in society. It was an agreement that was reached without war, fighting, violence, or compulsion; it was an agreement that all of its parties arrived at voluntarily due to their commitment to the shared principles contained therein, within the sphere of positive cooperation, the context of their conditions, and the various elements of the Medinan society. It was a step towards the realization of social peace based upon their mutual recognition of rights and responsibilities and of accepting the demands of their diversity, their various religious affiliations, benefits, and lifestyles. Medina was a multi-ethnic and multi-religious society that was not founded as the result of a conquest. There, the Prophet composed a document governing the relations between the Muslims and other religious communities that would come to be known as “the Constitution of Medina.” This document was, for all intents and purposes, a just constitution that established a type of contractual citizenship. It affirmed that those who were under its authority were one, cohesive, unified polity with all of its citizens enjoying equal rights and having the same duties. This document affirmed the unity of the society in terms of religious pluralism and freedom of religion, but, despite its obvious importance, it has not garnered much study. Revival of Medina Charter and to make thorough study to be applicable to our constitution is rather very important factor nowadays. That is why a major conference was hosted in Marrakesh in the Kingdom of Morocco early this year of 2016. A large number of personals from more than 100 predominantly Muslim countries participated in this conference. It called upon other scholars of the world to initiate more on this concern. The Objective of this study is to revive Medina Charter for the modern day Islamic City planning which would enable the states to develop better and more appropriate planning methods for pluralistic Islamic societies and highlight the importance of Marrakesh Declaration. A qualitative method will be implemented in this study with content analysis method.